2007
DOI: 10.1111/j.0030-1299.2007.15290.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistant invaders can convey benefits to native species

Abstract: Introduced species are recognized as a major threat to native species. One factor that facilitates their spread is that they are often resistant to natural enemies of their native competitor. Negative effects of the invaders are often documented, but invaders may also convey benefits to the natives if they interfere with the native hostparasite interactions. If invaders act as resistant targets for the native parasites, they may reduce the density of the infectious transmission stages ('dilution effect') and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 38 publications
4
65
0
Order By: Relevance
“…Chernin 1968;Chernin & Perlstein 1971), parasitologists have found that (i) the addition of a broad range of non-hosts (but not shells or inanimate objects) interferes with the ability of free-living parasites (trematode miracidia and cercariae) to locate and infect target hosts, (ii) the extent of interference varies among non-host species and with the ratio of hosts to non-hosts, and (iii) the addition of non-hosts can cause an increase or decrease in cercarial production among infected hosts, probably as a function of miracidial exposure level (e.g. owing to intra-snail competition by trematodes ;Upatham 1972;Upatham & Sturrock 1973;Frandsen & Christensen 1977;Christensen 1980;Moné et al 1986;Combes & Moné 1987;Moné 1991;Chipev 1993;Kopp & Jokela 2007;Thieltges et al 2008a,b). The ecological mechanisms underlying the decoy effect involve diversion of infectious parasites away from the target host by non-hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Chernin 1968;Chernin & Perlstein 1971), parasitologists have found that (i) the addition of a broad range of non-hosts (but not shells or inanimate objects) interferes with the ability of free-living parasites (trematode miracidia and cercariae) to locate and infect target hosts, (ii) the extent of interference varies among non-host species and with the ratio of hosts to non-hosts, and (iii) the addition of non-hosts can cause an increase or decrease in cercarial production among infected hosts, probably as a function of miracidial exposure level (e.g. owing to intra-snail competition by trematodes ;Upatham 1972;Upatham & Sturrock 1973;Frandsen & Christensen 1977;Christensen 1980;Moné et al 1986;Combes & Moné 1987;Moné 1991;Chipev 1993;Kopp & Jokela 2007;Thieltges et al 2008a,b). The ecological mechanisms underlying the decoy effect involve diversion of infectious parasites away from the target host by non-hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Coevolution with specific genetic interactions has been documented between several invertebrate species and their parasites, including Daphnia waterfleas with bacterial parasites [11], the bumble-bee Bombus terrestris with trypanosomes [27] and P. antipodarum snails with trematodes [17]. While parasite hatching may not be host-specific [28], the snail immune system may be specific. Few parasites were given a second chance.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the role of parasitism in animal invasions has been considered in cases where the invasive species has been capable of sharing parasites with the native species, either amplifying them or acting as a sink for the parasites (Prenter et al 2004, Kopp and Jokela 2007, Thieltges et al 2009, Paterson et al 2011). There are also well-documented cases where parasites are used as weapons of competition (Prenter et al 2004, Haddaway et al 2012, whereby invasive species are either spreading a new parasite to the native species, or the invasive species benefit from being resistant to parasites debilitating the native species.…”
Section: Discussionmentioning
confidence: 99%